Analysis of Capture Fisheries Business at Limboto Lake - Febriyani Abdullah; Alfi Sahri Remi Baruadi; Zhulmaydin Chair Fachrussyah (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the feasibility of fishermen's business and possible development in Lake Limboto, Gorontalo Province. The study was conducted from February to August 2016. This study used direct observation and interviews with fishermen and field observations. The results showed that financially the fishing effort in Lake Limboto was feasible to be developed, this was proven by the acquisition of R / c Ratio and payback period of each type of fishing gear used. Keywords: Fishing gear; fisherman; development; feasibility; Lake Limboto